OPTIMIZATION OF THE EDUCATIONAL PROCESS BASED ON REPRESENTATIVE SYSTEMS - Jasmina Abdualiyeva (Modern American Journals, 2025)
This article analyzes the issue of optimizing the educational process based on the concept of representational systems from the point of view of neuropedagogical approaches. Representational systems — that is, individual perception methods based on visual, auditory, kinesthetic and other sensory types — directly affect the process of students' assimilation of knowledge. This article examines the possibilities of increasing educational effectiveness by identifying the dominant representational system of students, selecting appropriate educational strategies for it, and organizing the educational process in a person-oriented manner. Based on the theoretical foundations of neuropedagogical science and the scientific views presented in the framework of modern research, the importance of an individual approach to education is highlighted and practical recommendations are given.
Keywords: Neuropedagogy, representational systems, visual, auditory, kinesthetic methods, individual approach, educational process, educational effectiveness, sensory systems, learning strategies, person-centered education, knowledge acquisition.